2020
DOI: 10.24114/pjkr.v4i2.14713
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hypnotherapy on the Coaching Achievement of Athletes in the Sports Branch of Jump and Throw Numbers

Abstract: This research used experimental design in the form of one group pre-post design, aimed to find out; the effect of hypnotherapy on fostering athletes' achievements in jump and throw sports. The population was all athletes in the athletic sport of jumping and throwing of 23 people. The technique of determining the sample by positive sampling, while the technique of data analysis used descriptive frequency analysis and paired sample test analysis (paired t-test) through the SPSS program version 20.00 at a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…By combining hypnosis with physical exercise, hypnosis aims to optimise athletes' awareness, concentration, and focus. Recent research examining hypnosis has found positive effects in sports such as football (Barker et al, 2013), golf (Pates, 2013), and athletics (Amirzan & Kasih, 2020), as well as other sports including shooting (Mattle et al, 2020), in both controlled and single case studies. However, these studies have limitations, such as small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…By combining hypnosis with physical exercise, hypnosis aims to optimise athletes' awareness, concentration, and focus. Recent research examining hypnosis has found positive effects in sports such as football (Barker et al, 2013), golf (Pates, 2013), and athletics (Amirzan & Kasih, 2020), as well as other sports including shooting (Mattle et al, 2020), in both controlled and single case studies. However, these studies have limitations, such as small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…mungkin dan terus belajar untuk mengembangkan kemampuan sesuai situasi dan kondisi yang dihadapi serta tantangan-tantangan yang terus berubah-ubah. Guru yang telah siap dalam mengajar salah satunya terlihat dengan kestabilan emosi dalam menghadapi berbagai permasalahan yang sering dijumpai baik dalam kelas, sekolah, maupun di rumah (pribadi).Kesiapan sikap dan emosi terlihat dari sikap bertanggung jawab yang dimiliki guru seperti berusaha mencari informasi terkait kegiatan pembelajaran dan melaksanakan pembelajaran yang inovatif(Amirzan et al, 2019;Kusuma, 2020). Kesiapan aspek sikap dan kesiapan emosional pada semua guru sampel berada pada kategori siap dan sangat siap.…”
unclassified